Are the police racist? A critical assessment of the literature on police minority relations. - McMullen, Shirley M. (University of Ottawa (Canada), 1994)
This thesis proposes that the systemic differential treatment of aboriginal and racial minority peoples in the criminal justice system is at least partly attributed to police racism. Discrimination, which refers to the negative treatment toward out-groups (Elliot and Fleras, 1992:330), is systemic in policing and not isolated to racial minorities. The lower class and others considered deviant are also routinely discriminated against. However, the visibility of racial minorities and aboriginal peoples makes them particularly susceptible to police actions. Because the role of policing necessitates the identification of not only criminals but also potential criminals, this identification must have visible characteristics, or cues. Consequently, the police officer comes to develop these visible characteristics to identify criminals. It is thus the visibility of racial minorities which results in their being categorized as criminal and subsequently the focus of police suspicion. Chapter one reviews the literature in other democratic countries to determine the role of police decision-making in the over-representation of aboriginals and racial minorities in the criminal justice system. Establishing the over-representation of aboriginal peoples and visible minorities in Canada, chapter two examines various explanations for this. Chapter three presents the allegations of police racism by visible minority and aboriginal peoples. (Abstract shortened by UMI.)
Keywords: Sociology, Criminology and Penology.